Idaratul Jenazah (i-Jenazah) - M. Muhsin; I. Nur Hafiz; A.M. Ahmad Jauhari (Universiti Sains Islam Malaysia, 2024)
In this application, we would like to change the perceptions of how to management of body into more relevant way in the same sequence of technology in the Information and Communication Technology (ICT) era. Nowadays, the knowledge of management of body on a certain village or city is fully depending on Imam and Masjid or Surau committee only. Thus, we would like to use current technology that already existed such as flash, to help Muslim community to better understand in management of body. Hopefully with this application, it will help and guide Muslim community ,o learn and understand the right mean of management of body and practice it when involve in management of body some other time.